The Role of Santri Organizations in Realizing the Vision and Mission of Islamic Boarding Schools - Rieke Diana Putri; Azizah Hanum OK; Mohammad Al Farabi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This research aims to find out how student organizations provide support to students in Islamic boarding schools, especially in achieving the vision and mission of Islamic boarding schools. This study uses a qualitative method with a phenomenological approach, which is based on subjective or phenomenological experiences experienced by individuals. This research then collects more information and is descriptive, or information obtained from informants. This research took place at Modern Islamic Boarding Schools in Asahan Regency, namely the Daar Al Uluum Asahan Modern Islamic Boarding School. The results of the study found that the role of the santri organization in realizing the vision and mission of the Islamic boarding school (a study in modern Islamic boarding schools throughout Asahan Regency) namely the work program of the santri organization is made according to the conditions and needs of each Islamic boarding school such as the fields of security, language, manners, teaching, worship, cleanliness, kitchen, facilities and infrastructure, sports and health. The implementation of the work program runs well according to the Islamic boarding school education calendar and the results of the annual meeting involving supervisors, administrators, and senior students.